Efficacy and pharmacokinetics of a modified acid-labile docetaxel-PRINT® nanoparticle formulation against non-small-cell lung cancer brain metastases. (August 2016) - Sambade, Maria; Deal, Allison; Schorzman, Allison; Luft, J Christopher; Bowerman, Charles; Chu, Kevin; Karginova, Olga; Swearingen, Amanda Van; Zamboni, William; DeSimone, Joseph; Anders, Carey K
Aim: Particle Replication in Nonwetting Templates (PRINT ® ) PLGA nanoparticles of docetaxel and acid-labile C2-dimethyl-Si-Docetaxel were evaluated with small molecule docetaxel as treatments for non-small-cell lung cancer brain metastases.Materials & methods: Pharmacokinetics, survival, tumor growth and mice weight change were efficacy measures against intracranial A549 tumors in nude mice. Treatments were administered by intravenous injection.Results: Intracranial tumor concentrations of PRINT-docetaxel and PRINT-C2-docetaxel were 13- and sevenfold greater, respectively, than SM-docetaxel. C2-docetaxel conversion to docetaxel was threefold higher in intracranial tumor as compared with nontumor tissues. PRINT-C2-docetaxel increased median survival by 35% with less toxicity as compared with other treatments.Conclusion: The decreased toxicity of the PRINT-C2-docetaxel improved treatment efficacy against non-small-cell lung cancer brain metastasis.